Družinska medicina in uporabniki komplementarne in alternativne medicine - Kersnik, Janko (Zdravstveno varstvo, 2006)
The article presents some data on the use of various forms of complementary and alternative medicine (CAM) in Slovene family practice patients. The usage rates range from 6% to 37 %, which is comparable to the data from the literature. Doctors' attitude towards CAM and the possibility of coexistence of alternative and conventional medicine are two important issues addressed byfamily practice. Only 28.9 % of patients consult their family doctors about the use of CAM, and 38.2 % report the use of alternative medicine to their doctors. In 23.8% of cases, doctors themselves recommended the use of some form of alternative treatment The level of patient satisfaction with family practice does not seem to predict the use of CAM. In only 34 % of cases wereCAM healers interested in the history of previous conventional treatment. They referred 20.1 % of their patients back to family practitioners, and in 4.6 % of cases they discouraged the use of conventional therapies.
Keywords: alternativna medicina; družinska medicina; komplementarna medicina